PERANANiDINAS PERHUBUNGANiKOTA PEKALONGANiDALAM MENINGKATKANiPELAYANANiMASYARAKAT DIiBIDANG ANGKUTANiKOTA - Indra Kertati; S. Hardi Widiyanto (Jurnal Media Administrasi, 2021)
In itsiiefforts to improveiipublic servicesiiin the fieldiiof urbaniitransportation, the Departmentiiof Transportation isiirequired toiimaximize itsiirole, namely as a policy maker (regulator), facility provider (facilitator), and as a supervisor (evaluator). As intended, the target to be achieved by the Department of Transportation is the creation of transportation services that are effective, integrated, sufficient capacity, affordable rates, orderly, orderly, smooth and fast, safe, secure, easy, timely and comfortable and efficient in a unified national transportation network. . This study uses aiidescriptive researchiimethod with a qualitativeiiapproach. Sourcesiiof data usediiare primaryiidata and secondary data. Dataiicollection techniquesiiwith observation, interviewsiiand documentation. Theiiresearch instrumentsiiused were theiiresearchersiithemselves, interviewiiguides, andiifield notes.ii Theiiresults of this study are (1) Pekalongan CityiiTransportationiiService has an important role as an agency that handles the transportation sector in general. Iniiconnection with efforts toiiimprove services to theiicommunity, one of the efforts made by the Pekalongan City Transportation Service is to improve services to theiicommunity in the field of city itransportation services, (2) In an effort to improve services, the community's response to city transportation services in Pekalongan City reaped positive and negative responses. (3) There are supporting factors as well as inhibiting factors from the Pekalongan City Transportation Service in improving public services in the field of urban transportation. Supporting factors include, adequateiiresource capabilities, the communityiiis required to playiian active role suchiias using cityiitransportation in an orderlyiimanner andiinot stoppingiipublic transportationiiin anyiiplace, asiiwelliias providingiiadequate facilitiesiiand infrastructure. Whileiithe inhibitingiifactors are related to competition in theiibusiness worldiibetween publiciitransportationiiand privateiivehicles and theiiexistence of other transportationiiservices.